Cotton and polyester treated with tragacanth gum loaded with clove essential oil Nanoemulsion for mosquito repellent - Azlan Kamari, Norjan Yusof (Tanjung Malim, 2024)
Cotton and polyester treated with tragacanth gum loaded with clove essential oil Nanoemulsion for mosquito repellent by Azlan Kamari, Norjan Yusof